Optimal Conditioning of Growth Media White Oyster Mushroom (Pleurotus ostreatus) to Increase Productivity - Hodijat, Asep; Nurlina, Elin (RA Journal Of Applied Research, 2023)
The cultivation of white oyster mushrooms is the difficulty of making mushroom seedlings, especially the technology is quite expensive and the nature of mushroom growth which has two different temperatures, namely low temperature when making seedlings and medium temperature when forming mushroom fruit bodies. Therefore optimal conditioning of the growth medium of white oyster mushroom (pleurotus ostreatus) to increase production yield. Judging from the business opportunity, oyster mushrooms are among the most popular compared to other types of mushrooms. In general, white oyster mushroom cultivation is considered easy to do, as long as the living environment is well considered. Although mushrooms are more optimal to grow in the highlands (cool areas), cultivation in the lowlands can also be done, as long as the place of maintenance is conditioned the same as its natural habitat.